Comparative analysis of managing beaches as a recreational resource in Croatia and Portugal - Kovačić, Mirjana, inženjerka pomorskog prometa (Array, 2020)
Beaches are natural resources that substantially enrich the tourist offer. They are an extremely valuable resource, with economic, recreational, and health significance. Beaches are a place for socializing, sports and enjoying (sun, sea, and sand tourism product). Because of their different roles, especially urban and hotels/resorts beaches, they are exposed to various and numerous negative impacts caused by natural changes and human activity. Beaches should not be just an object for commercial use, as their meaning for people is much wider. This research focuses on managing and protecting beaches that require social responsibility due to their determining role in the national economies. The guidelines for effective management primarily refer the necessity of developing intellectual resources, the coordination between institutions, ensuring pro-activity and being holistic oriented in managing beaches. Scientists and professionals need to recognize their importance and take action to preserve this valuable asset for future generations. In that sense, the purpose of this research is to analyse the legal regulation and to highlight the differences and similarities between two countries, Croatia and Portugal, which due to their physical geography, climate and tourism activity, are based mainly on beach-related activities.